Ethical behaviors by leaders act as a stimulant to the wellbeing of employees by restraining workplace embitterment - Saleem, Ammara; Bashir, Mohsin; Abrar, Muhammad (Frontiers in Public Health, 2022)
Prior studies have revealed that leaders’ ethical behaviors significantly influence employees’ well-being. However, it’s unclear how to increase the positive impact of leaders’ ethical behaviors on employees’ well-being by overseeing the negative workplace emotion. So, this study examines the salient concern of leaders’ ethical behaviors that affect employees’ negative emotions (workplace embitterment) and, consequently, their well-being according to appraisal theories of emotions. The study also investigates the active role of followers’ core self-evaluation in moderating the impact of leaders’ ethical behaviors on followers’ emotions and well-being via the mediational chain. Data is collected in two-time intervals with six weeks interims through a structured questionnaire from 398 academics of public sector universities in Pakistan. The structured equation modeling and Process Macro 2017 are the tools for data analysis. The study's findings show that: (1) leaders' ethical behaviors have a negative impact on employee workplace embitterment; (2) workplace embitterment completely mediates the association between leaders' ethical behaviors and employee well-being; and (3) when leaders don't exhibit ethical behaviors, workplace embitterment is lessened by employees' high core self-evaluations. In addition, the study findings also reveal that employees’ core self-evaluation moderates the effect of leaders’ ethical behaviors through workplace embitterment. This study validates the significant role of a leader’s ethical behaviors in nourishing employee wellbeing by preventing negative emotions. The study is also significant as it examines how followers attribute core self-evaluation: (1) can be a substitute for leaders’ ethical behaviors; and (2) can actively modify the effect of leaders' ethical behaviors on followers' negative emotions and then well-being. The study also discussed its contributions in theory and to organizations.